PENGARUH LEADER MEMBER EXCHANGE DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT TECTONA CIPTA NIAGA - Muhammad Fahreza; Syarifuddin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the influence of Leader Member Exchange and Organizational Culture on the Performance of Employees at PT Tectona Cipta Niaga. Leader Member Exchange refers to the quality of the relationship between leaders and team members, which is hypothesized to have a significant impact on employee work effectiveness. Additionally, Organizational Culture, encompassing values, norms, and practices implemented within a company, is considered a key factor influencing individual performance. This research employs a quantitative method using nonprobability sampling with a saturated sample for data collection, involving 60 respondents from PT Tectona Cipta Niaga. The data analysis techniques include descriptive analysis and multiple linear regression analysis. Partial research results show that Leader Member Exchange has a positive and significant influence on employee performance, and Organizational Culture also has a positive and significant impact on employee performance. Simultaneously, Leader Member Exchange, Organizational Culture, and employee performance have a significant impact on employee performance, this shows that the influence of the independent variables, Leader Member Exchange and Organizational Culture, have a 71% influence on the dependent variable, employee performance, while the remaining 29% is influenced by other factors not examined in this study.